2018
DOI: 10.18805/ijare.a-4812
|View full text |Cite
|
Sign up to set email alerts
|

Effect of herbicides on the activity of soil enzymes urease in maize crop

Abstract: A field experiment was conducted to study the effect of pre-emergence, post emergence and combination of atrazine with post emergence herbicides on soil enzyme urease activity(expressed as µg of NH4+ released g-1 soil h-1) at College Farm, College of Agriculture ,Professor Jayashankar Telangana State Agricultural University (PJTSAU), Rajendranagar, Hyderabad, India during kharif 2014. The experiment was laid out in randomized block design (RBD) using six herbicide treatments un weeded control and hand weeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Riah et al (2014) classified herbicides as stimulants with positive effect and inhibitors with negative effect, formesafen a class of herbicide has stimulatory effect on acid and alkaline phosphates and mixed effect on ureases was found by Zang et al (2014). Aruna et al (2018) have observed similar effect with respect to urease activity. Pre-emergence herbicides have shown stimulation and post emergence herbicides mixed responses…”
Section: Treatments Tsupporting
confidence: 60%
“…Riah et al (2014) classified herbicides as stimulants with positive effect and inhibitors with negative effect, formesafen a class of herbicide has stimulatory effect on acid and alkaline phosphates and mixed effect on ureases was found by Zang et al (2014). Aruna et al (2018) have observed similar effect with respect to urease activity. Pre-emergence herbicides have shown stimulation and post emergence herbicides mixed responses…”
Section: Treatments Tsupporting
confidence: 60%
“…The sand content varied from 39.7 to 60.4% and 77.2 to 90.7% with mean values 53. 15 Decreasing DI value of EC +42.37 percent was measured in IC-HAPI.…”
Section: Results and Discussion Comparison In Fls Physical Parameter mentioning
confidence: 90%
“…The temperature drift and the systematic biased is considered to be rectangular distribution that has limited value governed the estimated behaviour (figure 8). zero current [4,5,6]. For the determination of the electrical resistance, an electrical measurement must be carried out for which a measurement current must be fed through the sensor (figure 5).…”
Section: Driftmentioning
confidence: 99%